Therapeutic action : an earnest plea for irony / Jonathan Lear. - Lear, Jonathan. (Other Press, 2003)
"The book is not merely about the therapeutic action of psychoanalysis; it is an enactment of conceptual therapy. It is written as an invitation to clinicians - psychologists, psychoanalysts, psychiatrists - to renew their own engagement with the fundamental concepts of their practice. To that end, the book investigates the concepts of subjectivity and objectivity that are appropriate for psychoanalysts, the concept of internalization and of transference. There is also an extended discussion of the theories of Hans Loewald and Paul Gray - and how they do and do not fit together. The very idea that love, or Eros, could be a drive - as Freud postulated - is given a new interpretation." "Therapeutic Action will be of interest to anyone concerned with the central concepts of psychoanalysis. And, indeed, to anyone interested in how conversation can bring about fundamental psychic change."--BOOK JACKET.